A Multilevel Analysis of the Chinese Super League: Examining the Game Level and Home Team Level Determinants of Stadium Attendance. Issue 4 (2nd December 2022) - Li, Shanshan; Ryu, Yoonji; Kim, Hansol
Abstract: The Chinese Super League (CSL) is the top tier football league in China and over the past 10 years has expanded rapidly in terms of popularity, brand strength, and name recognition. Despite the CSL's rapid development, limited empirical research has been done to examine the league and what drives demand in attending the games. Thus, in order to gain a better understanding of CSL and identify unique patterns of demand for professional sports leagues in China, this study used data from the 2017–2019 CSL regular seasons to examine the relationship between various stadium determinants and game attendance. Moreover, the nested structure found in attendance data was considered, thus adopting multilevel modeling (MLM) to analyze game level and home team level variables to predict stadium attendance in the CSL. Our findings reveal that 12 variables significantly influenced attendance, with variables related to home teams showing more relevance to explaining stadium attendance than game level variables.